Comparative Evolutionary Histories of Kisspeptins and Kisspeptin Receptors in Vertebrates Reveal Both Parallel and Divergent Features - Pasquier, Jérémy; Lafont, Anne-Gaëlle; Tostivint, Hervé; Vaudry, Hubert; Rousseau, Karine; Dufour, Sylvie (Frontiers in Endocrinology, 2012)
During the past decade, the kisspeptin system has been identified in various vertebrates, leading to the discovery of multiple genes encoding both peptides (Kiss) and receptors (Kissr). The investigation of recently published genomes from species of phylogenetic interest, such as a chondrichthyan, the elephant shark, an early sarcopterygian, the coelacanth, a non-teleost actinopterygian, the spotted gar, and an early teleost, the European eel, allowed us to get new insights into the molecular diversity and evolution of both Kiss and Kissr families. We identified four Kissr in the spotted gar and coelacanth genomes, providing the first evidence of four Kissr genes in vertebrates. We also found three Kiss in the coelacanth and elephant shark genomes revealing two new species, in addition to Xenopus, presenting three Kiss genes. Considering the increasing diversity of kisspeptin system, phylogenetic and synteny analyses enabled us to clarify both Kiss and Kissr classifications. We also could trace back the evolution of both gene families from the early steps of vertebrate history. Four Kissr and four Kiss paralogs may have arisen via the two whole genome duplication rounds (1R & 2R) in early vertebrates. This would have been followed by multiple independent Kiss and Kissr gene losses in the sarcopterygian and actinopterygian lineages. In particular, no impact of the teleost-specific 3R could be recorded on the numbers of teleost Kissr or Kiss paralogs. The origin of their diversity via 1R & 2R, as well as the subsequent occurrence of multiple gene losses, represent common features of the evolutionary histories of Kiss and Kissr families in vertebrates. In contrast, comparisons also revealed un-matching numbers of Kiss and Kissr genes in some species, as well as a large variability of Kiss/Kissr couples according to species. These discrepancies support independent features of the Kiss and Kissr evolutionary histories across vertebrate radiation.